0252 Actigraphic Sleep is Associated with Bone Mineral Density and Bone Turnover in Young Adults. (27th April 2018) - Petrov, M E; Whisner, C M; Mahmood, T M; Castillo, L F; Richardson, J; Gupta, R
Abstract: Introduction: Short and long sleep duration are associated with lower bone mineral density (BMD) in middle-aged to older populations. Few studies have investigated this relationship using wrist actigraphy among young adults who continue to develop bone mass through age 30. The objective of this study was to identify associations between actigraphic sleep measures, BMD, and markers of bone turnover among young adults. Methods: In this cross-sectional study, 44 young adults (age M =20.3y, Range:18-24y; 50% women) participated with a body mass index (BMI) of 18.5–29.9 kg/m 2 and no prior history of sleep, eating, malabsorptive, autoimmune, or movement disorders. Participants wore a wrist actigraph for 7 nights. Average total sleep time (TST; measured continuously and in quartiles), sleep efficiency (SE), bedtime, final awakening, and time in bed (TIB) during the main sleep period were computed. Nap bedtime, wake-up time, TST, SE, and TIB also were computed. Participants underwent dual-energy X-ray absorptiometry (Lunar iDXA) of the lumbar spine (L1-L4) and hip. In a subsample (n=30), serum concentrations of osteocalcin (OC; formation marker) and cross-linked N-Telopeptide of Type I Collagen (NTXI; resorption marker) were assayed by ELISA. Multiple regressions of bone health and actigraphic sleep variables were analyzed, adjusting for sex and BMI. Adjusted ANOVAs examined the association between TST quartiles and bone health variables. Results: Lumbar and hip BMD z-scores were 0.395±.955 and 0.502 ± 1.053, respectively. OC and NTXI concentrations were 13.0 ± 4.7ng/ml and 11.6 ± 2.1ng/ml, respectively. Mean nightly TST and SE were 397.4 ± 51.5min and 86.3 ± 6.0%, respectively. After adjustment, TST was positively associated with femoral neck BMD ( F [3, 39]=3.43, p =0.03, β=.37, p =.02). Participants with TST at the lowest quartile (<6hr) had lower spinal BMD compared to all other quartiles ( F [1, 40]=8.23, p =0.007). Of the participants who took naps ( n =16), greater nap TIB was positively associated with NTXI ( r =.53, p =.04). No other associations were significant. Conclusion: Among young adults, greater TST was associated with greater BMD of the spine and femoral neck indicating better bone health and reduced risk for fracture. Greater time spent napping was associated with greater bone resorption. Support (If Any): N/A.